Urgensi Tafsir Al-Qur`An dan Syarah Hadis bagi Juru Dakwah - Zulkarnaini Zulkarnaini (Universitas Islam Negeri Imam Bonjol Padang, 2018)
Da'wah means inviting people to Allah, by following His path that He shows in His religion and shari'ah, namely Islam. In other terms, preaching means inviting people to follow the messages of Allah SWT contained in the Qur'an according to the guidance of the Sunnah of the Prophet which contains the books of hadith. Preaching should have to refer to the Qur'an or the hadith of the Prophet. Where are the Qur'anic and Hadith texts in Arabic. To help Indonesian Muslims in understanding the intent contained in the verses of the Qur'an and the traditions of the Prophet, competent parties have tried to translate these two sources of Islamic teachings. By reading this translation, it can at least attract the attention of Muslims to find out more about the intent of the message contained in the Arabic text. This condition on the one hand is enough to help Indonesian Muslims to understand the Qur'anic and Hadith texts as well as certain readings in worship, but on the other hand it often creates problems, which is wrong in understanding the Qur'anic texts and the Prophet's hadith. For the writing explains the importance of a missionary interpreter to guide the Qur'an and the Prophet's hadith in preaching.